Impacts of loss of free-flowing rivers on global freshwater megafauna. (November 2021) - He, Fengzhi; Thieme, Michele; Zarfl, Christiane; Grill, Günther; Lehner, Bernhard; Hogan, Zeb; Tockner, Klement; Jähnig, Sonja C.
Abstract: The fragmentation of free-flowing rivers (FFRs) through major infrastructure development remains a pivotal threat to global freshwater biodiversity. More than 3400 large hydropower dams (>1 MW) are either planned or under construction, posing threats to freshwater megafauna (i.e., freshwater animals that can reach 30 kg). Here, we investigate the global patterns of river connectivity within distribution ranges of freshwater megafauna and explore how these patterns could change in the future. We found that the susceptibility of freshwater megafauna to reduced river connectivity in different dimensions depends on their life history. Freshwater megafauna taxa with a short accumulated length or low percentage of FFRs in their distribution ranges are more likely to be threatened. On average, there is higher freshwater megafauna richness in FFRs with proposed dams than in rivers that would remain free-flowing in the future or that are already fragmented. If all the proposed dams were built, 94 (18.9%) out of 497 remaining FFRs >500 km that provide habitat for freshwater megafauna would lose their free-flowing status. Our results highlight the reduced connectivity of rivers currently inhabited by freshwater megafauna and the future intensification of river fragmentation in megafauna-rich basins. Research and conservation efforts, including life-history studies, identification of critical habitats, updates of IUCN Red List assessments, advanced communication of the potential impacts on ecosystem services and livelihoods of affected communities, and strategic siting, design, and operations of proposed dams are urgently needed to safeguard freshwater megafauna and overall freshwater biodiversity. Highlights: Freshwater megafauna taxa with a short length of FFRs in their ranges are more likely to be threatened. FFRs that would be fragmented by proposed dams have high freshwater megafauna diversity. 262 proposed dams are located on 75 current FFRs >500 km with freshwater megafauna. Fragmentation of rivers inhabited by threatened megafauna would be intensified.